2014
DOI: 10.1371/journal.pone.0089254
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Medical Student Empathy and Personality: A Multi-Institutional Study

Abstract: BackgroundMore empathetic physicians are more likely to achieve higher patient satisfaction, adherence to treatments, and health outcomes. In the context of medical education, it is thus important to understand how personality might condition the empathetic development of medical students. Single institutional evidence shows associations between students' personality and empathy. This multi-institutional study aimed to assess such associations across institutions, looking for personality differences between st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
100
5
9

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(119 citation statements)
references
References 38 publications
5
100
5
9
Order By: Relevance
“…This is a low cost alternative which has great potential benefits 12 . In Portugal 13 , it was also discovered that personality has a significant predictive value on empathy and is closely associated with the ability to be open to new experiences and students' kindness. This suggests paying attention to personality.…”
Section: Empathy In Health Carementioning
confidence: 99%
“…This is a low cost alternative which has great potential benefits 12 . In Portugal 13 , it was also discovered that personality has a significant predictive value on empathy and is closely associated with the ability to be open to new experiences and students' kindness. This suggests paying attention to personality.…”
Section: Empathy In Health Carementioning
confidence: 99%
“…Scores of the JSE have also been linked to the “big five” personality factors such as Agreeableness, Openness to Experience, Conscientiousness, and Extraversion in medical students in Portugal (Costa et al 2014). …”
Section: Introductionmentioning
confidence: 99%
“…(15,16) In one crosssectional study of medical students, agreeable individuals were shown to be more empathetic than non-agreeable individuals. (17) Medical students were also more extroverted compared to their non-medical peers. It is known that both extroverts and introverts make good doctors.…”
Section: Discussionmentioning
confidence: 95%